ANALISIS KEMAMPUAN HIGHER ORDER THINGKING SKILLS (HOTS) PESERTA DIDIK PADA PEMBELAJARAN MATEMATIKA KURIKULUM MERDEKA - Netriwati; Anggraini, Fitria; Niatapia, Susi; Cahayanti, Adinda Zein; Safitri, Shanria; Nendra, Fadly (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this study is to examine how students use HOTS Higher Order Thinking Skills (HOTS) when learning mathematics using the Independent Curriculum. "Twenty-five students of class XII IPA MA Al Hikmah Bandar Lampung became the subjects of this qualitative descriptive study. In-depth interviews and HOTS-based tests were used to collect data. The Miles HOTS Huberman model was used in the data analysis process, which includes data reduction, data presentation, HOTS conclusion drawing". According to the findings, 24% of students are included in the high group, 48% in the middle category, HOTS 28% in the low category. All indicators of HOTS analysis, assessment, HOTS creation are filled by highly capable students. Students in the middle group, on the other hand, are able to understand the problem but have difficulty in assessing HOTS development solutions. Low-ability students show significant challenges in understanding HOTS problems and choosing the right solution. These results indicate that students' HOTS skills are still below the HOTS standard and require improvement by using appropriate teaching methods.